Reconsultation, self-reported health status and costs following treatment at a musculoskeletal Clinical Assessment and Treatment Service (CATS): a 12-month prospective cohort study. Issue 10 (12th October 2016) - Roddy, Edward; Jordan, Kelvin P; Oppong, Raymond; Chen, Ying; Jowett, Sue; Dawes, Peter; Hider, Samantha L; Packham, Jon; Stevenson, Kay; Zwierska, Irena; Hay, Elaine M
Abstract : Objectives: To determine (1) reconsultation frequency, (2) change in self-reported health status, (3) baseline factors associated with reconsultation and change in health status and (4) associated healthcare costs and quality-adjusted life-years (QALYs), following assessment at a musculoskeletal Clinical and Assessment Treatment Service (CATS). Design: Prospective cohort study. Setting: Single musculoskeletal CATS at the primary–secondary care interface. Participants: 2166 CATS attenders followed-up by postal questionnaires at 6 and 12 months and review of medical records. Outcome measures: Primary outcome was consultation in primary care with the same musculoskeletal problem within 12 months. Secondary outcome measures were consultation at the CATS with the same musculoskeletal problem within 12 months, physical function and pain (Short Form-36), anxiety and depression (Hospital Anxiety and Depression Scale), time off work, healthcare costs and QALYs. Results: Over 12 months, 507 (38%) reconsulted for the same problem in primary care and 345 (26%) at the CATS. Primary care reconsultation in the first 3 months was associated with baseline pain interference (relative risk ratio 5.33; 95% CI 3.23 to 8.80) and spinal pain (1.75; 1.09 to 2.82), and after 3–6 months with baseline assessment by a hospital specialist (2.06; 1.13 to 3.75). Small mean improvements were seen in physical function (1.88; 95% CI 1.44 to 2.32) and body pain (3.86; 3.38 to 4.34) at 6 months. Poor physical function at 6 months was associated with obesity, chronic pain and poor baseline physical function. Mean (SD) 6-month cost and QALYs per patient were £422.40 (660.11) and 0.257 (0.144), respectively. Conclusions: While most patients are appropriate for a 'one-stop shop' model, those with troublesome, disabling pain and spinal pain commonly reconsult and have ongoing problems. Services should be configured to identify and address such clinical complexity.